Teaching While Black - Wood, Eben (Radical Teacher, 2020)
A review of Matthew E. Henry's Teaching While Black. Main Street Rag Publishing Company, 2020. Matthew E. Henry's slim, searing first book of poems, Teaching While Black, is composed of situations or "teaching moments" that have occured throughout his life and particularly in his career as a Black teacher at mostly white and privileged schools. Particularly timely after the recent police killings of Breonna Taylor, George Floyd, and others, the poems, and the moments each represents, highlight the intersection of race, class, and gender politics, exploring the conflicted meanings of place, position, and identity for a Black educator. These are challenging, insightful, and passionate poems that would be ideal reading for courses focused on these issues, particularly in conjunction with the BLM protests that coincide with the collection's publication and with helping students both to understand and resist the received positions that society, or educational institutions assign them.